2021
DOI: 10.1097/mpg.0000000000003357
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Symptoms Assessed With the CFAbd‐Score are Associated With Intestinal Inflammation in Patients With Cystic Fibrosis

Abstract: Objectives:This prospective study evaluated the relationship between fecal markers of intestinal inflammation and cystic fibrosis (CF)-associated abdominal symptoms. These were assessed using the CFAbd-Score, a CF-specific patient-related outcome measure developed and validated, following FDA guidelines.Methods:In feces from patients with CF (n = 41) and healthy volunteers (n = 27), concentrations of fecal calprotectin (FC), M2-pyruvate kinase (M2-PK), interleukins IL-1β, IL-6, IL-8, and neutrophilic elastase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Levels of single GI symptoms in pwCF, before ETI treatment initiation, were similar to those described in our previous studies, with predominant symptoms: pain, flatulence, smelly stools and frequency of bowel movements (Figure 2) (Tabori et al, 2017a;Jaudszus et al, 2019;Jaudszus et al, 2021). After ETI treatment, "Embarrassment due to GI symptoms" was increased but remained lower than those described by HCs.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Levels of single GI symptoms in pwCF, before ETI treatment initiation, were similar to those described in our previous studies, with predominant symptoms: pain, flatulence, smelly stools and frequency of bowel movements (Figure 2) (Tabori et al, 2017a;Jaudszus et al, 2019;Jaudszus et al, 2021). After ETI treatment, "Embarrassment due to GI symptoms" was increased but remained lower than those described by HCs.…”
Section: Discussionsupporting
confidence: 85%
“…More recently, we assessed intestinal inflammation in stool by faecal elastase, M2-pyruvate kinase (M2-PK), interleukins IL-1β, IL-6, IL-8, and neutrophil elastase (NE), together with the CFAbd-Score. Here we found that both, CFAbd-Scores and intestinal inflammation, most sensitively assessed by faecal elastase, are markedly higher in pwCF, compared to healthy controls (Jaudszus et al, 2021).…”
Section: Limitationsmentioning
confidence: 55%
See 3 more Smart Citations